1994
DOI: 10.1037/0735-7044.108.3.486
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic cholinergic system involvement in eyeblink classical conditioning in rabbits.

Abstract: A nicotinic cholinergic antagonist, mecamylamine (MEC), was administered to rabbits tested on eyeblink classical conditioning (EBCC) in the 750-ms delay paradigm for 10 90-trial sessions. Nicotinic receptors were measured in 3 brain regions in 5 treatment groups: paired conditioned stimulus-unconditioned stimulus (CS-US) presentations with (a) vehicle, young; (b) vehicle, older; (c) 0.5 mg/kg MEC, young; unpaired CS-US with (d) 0.5 mg/kg MEC, young; and (e) vehicle, young. Daily MEC injections disrupted acquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Blockade of a7 nAChRs by memantine may have decreased its efficacy in the model system of eyeblink classical conditioning. An antagonist to nAChRs, mecamylamine, significantly impaired eyeblink classical conditioning in young rabbits (Woodruff-Pak et al, 1994a), and a partial agonist of a7 nAChRs, GTS-21, improved eyeblink conditioning in older rabbits (Woodruff-Pak et al, 1994b).…”
Section: Experiments 2fcombined Effect Of Memantine + Galantamine or Mmentioning
confidence: 95%
See 1 more Smart Citation
“…Blockade of a7 nAChRs by memantine may have decreased its efficacy in the model system of eyeblink classical conditioning. An antagonist to nAChRs, mecamylamine, significantly impaired eyeblink classical conditioning in young rabbits (Woodruff-Pak et al, 1994a), and a partial agonist of a7 nAChRs, GTS-21, improved eyeblink conditioning in older rabbits (Woodruff-Pak et al, 1994b).…”
Section: Experiments 2fcombined Effect Of Memantine + Galantamine or Mmentioning
confidence: 95%
“…Eyeblink conditioning impairment in AD may reflect medialtemporal lobe atrophy and associated central nervous system cholinergic dysfunction that occurs early in the disease progression. Disruption of acetylcholine neurotransmission in the septohippocampal system impairs learning of the conditioned eyeblink response in young (Harvey et al, 1983;Solomon et al, 1983;Woodruff-Pak et al, 1994a) and older rabbits (Pak et al, 2002). Data also indicate that NMDA receptor activity is involved in the acquisition of classically conditioned eyeblink responses (Chen and Steinmetz, 2000;Churchill et al, 2001; Thompson and Disterhoft, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A great advantage of this behavioral assay is that it can quantitatively test the effects of a drug on humans as well as lower mammals. The neuronal cir Kem cuitry involved in this type of associative learning is relatively well understood, compared with some other forms of learning, and it has been demonstrated that conditioned learning is inhibited by a nicotinic antagonist, mecamylamine (Woodruff-Pak et al, 1994a). Several doses of GTS-21 were tested upon eye-blink conditioning.…”
Section: Behavioral Actions Of Gts-21mentioning
confidence: 99%
“…Identification of nicotinic cholinergic receptors as the receptors impaired in AD led us to test a nicotinic cholinergic antagonist and nicotinic agonists in the animal model of eyeblink classical conditioning. By using a very low-dosage level of mecamylamine in young rabbits so that nicotinic cholinergic receptors would be selectively inhibited, we demonstrated a role for nicotinic cholinergic receptors in eyeblink conditioning because the acquisition of CRs was severely disrupted (15). A synthesized analog of the marine natural product anabasine (16) called GTS-21 [3-(2,4-dimethoxybenzylidene)anabaseine] has been found to preferentially interact with ␣7 neuronal nicotinic receptors.…”
mentioning
confidence: 99%